Cuisine in transition? Organic residue analysis of domestic containers from 9th-14th century Sicily. Issue 3 (8th March 2023) - Lundy, Jasmine; Drieu, Lea; Orecchioni, Paola; Meo, Antonino; Aniceti, Veronica; Fiorentino, Girolamo; Primavera, Milena; Talbot, Helen; Molinari, Alessandra; Carver, Martin O. H.; Craig, Oliver E.
Abstract : From the 9th to 14th centuries AD, Sicily experienced a series of rapid and quite radical changes in political regime, but the impact of these regime changes on the lives of the people that experienced them remains largely elusive within the historical narrative. We use a multi-faceted lipid residue approach to give direct chemical evidence of the use of 248 everyday domestic ceramic containers from Islamic and post-Islamic contexts in western Sicily to aid our understanding of daily habits throughout this period of political change. A range of commodities was successfully identified, including animal fats, vegetable products, fruit products (potentially including wine) and plant resins. The study highlights the complexity of residues in early medieval Mediterranean society as, in many cases, mixtures of commodities were observed reflecting sequential cooking events and/or the complex mixtures reflective of medieval recipes. However, overall, there were no clear changes in the composition of the residues following the imposition of Norman control over the island and through subsequent periods, despite some differences between urban centres and rural sites. Thus, lending to the idea that post-Islamic populations largely flourished and benefited from the agricultural systems, resources and recipes left by their predecessors.